Probabilistic Elastic-plastic Fracture Mechanics Analysis of Propagation of Cracks in Pipes under Internal Pressure - Belaïd Mechab; Medjahdi Malika; Mokadem Salem; Serier Boualem (Fracture and Structural Integrity)
This study presents a three dimensional finite element method analysis of semi-elliptical surface cracks in pipes under internal pressure load. In the elastic–plastic case, estimates of the J-integral are presented for various ratios including crack depth to pipe thickness (a/t) and strain hardening index in the (R-O) Ramberg-Osgood (n).  Finally, failure probability is accessed by a statistical analysis for uncertainties in loads and material properties, and structural reliability and crack size. The Monte Carlo method is used to predict the distribution function of the mechanical response. According to the obtained results, we note that the stress variation and the crack size are important factors influencing on the distribution function of (J/Je).